Student stress and worry related to distance education during the COVID-19 pandemic - Jelena Zvekić-Svorcan; Jovana Šarenac; Milena Kovačević; Dragana Vukliš; Rastislava Krasnik; Andrijana Mikić; Jelena Mikov; Igor Mikov (Journal of Infection in Developing Countries)
Introduction: The Coronavirus Disease 2019 (COVID-19) pandemic has caused considerable stress and anxiety in the general population, especially among students. The objective of this study was to determine the stress and anxiety levels among medical rehabilitation students induced by distance education during the COVID-19 pandemic.